2016
DOI: 10.1111/ppe.12279
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Dietary Patterns are Associated with Lower Levels of Cardiometabolic Markers during Pregnancy

Abstract: Background-Elevated levels of cardiometabolic markers are characteristic of normal pregnancy; however, insulin resistance and increased glucose, triglyceride, and cholesterol levels can adversely influence maternal and child health. Diet is a modifiable behavior that could have significant impact on maternal cardiometabolic levels during pregnancy. We investigated the association between dietary patterns and cardiometabolic markers (glucose, insulin, insulin resistance (HOMA-IR), triglycerides, and cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 44 publications
(63 reference statements)
6
18
0
1
Order By: Relevance
“…The present study showed that this expected increase in maternal lipids was, further, promoted in women of C2, whose dietary preferences were associated with higher total lipid, monounsaturated and polyunsaturated fatty acids intakes, compared to C1. It is of interest to mention that in a very recent study 61 , higher blood total cholesterol levels were recorded in pregnant women following a dietary pattern characterized, among others, by higher intakes of fruits, vegetables, whole grains, and low-fat dairy. However, due to the strong influence of pre-pregnancy lipid levels and maternal hormonal status during pregnancy on lipid metabolism 59 , 62 , no clear biochemical interpretation may be advanced at least at this stage.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that this expected increase in maternal lipids was, further, promoted in women of C2, whose dietary preferences were associated with higher total lipid, monounsaturated and polyunsaturated fatty acids intakes, compared to C1. It is of interest to mention that in a very recent study 61 , higher blood total cholesterol levels were recorded in pregnant women following a dietary pattern characterized, among others, by higher intakes of fruits, vegetables, whole grains, and low-fat dairy. However, due to the strong influence of pre-pregnancy lipid levels and maternal hormonal status during pregnancy on lipid metabolism 59 , 62 , no clear biochemical interpretation may be advanced at least at this stage.…”
Section: Discussionmentioning
confidence: 99%
“…fetal growth, preterm birth and risk of asthma) ( 14 ) . Likewise DQ was associated with blood TAG ( 15 ) , pre-eclampsia ( 16 ) and fetal growth restriction ( 17 ) .…”
mentioning
confidence: 99%
“…Dietary patterns prior to and during pregnancy have also been shown to influence levels of serum lipids [ 28 , 29 ]. In particular, dietary patterns prior to pregnancy with relatively high intakes of discretionary foods such as cakes, snacks and candies, have been demonstrated to raise triglyceride levels, particularly in the second trimester [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, dietary patterns prior to pregnancy with relatively high intakes of discretionary foods such as cakes, snacks and candies, have been demonstrated to raise triglyceride levels, particularly in the second trimester [ 28 ]. Conversely, dietary patterns consistent with recommendations for following a DASH-type diet have shown negative associations with serum triglycerides [ 29 ]. DASH-type diets are characterized by high intakes of plant-based foods such as fruits and vegetables, and limited intakes of saturated fats and discretionary food choices [ 30 ].…”
Section: Discussionmentioning
confidence: 99%